Overview of Pelvic Ring Fracture Patients: Observational Study in the Emergency Department at Dr. Kariadi General Hospital, Semarang, Indonesia - Utomo, Gede Pambudi; Agus Priambodo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Although the incidence of pelvic fractures is only 7% of all trauma, the mortality reaches 21.5%. Management of pelvic fractures remains a challenge because it is often a polytrauma that requires multidisciplinary management and large resources. Knowledge of the characteristics of patients with pelvic fractures is expected to help in management and reduce mortality. Methods: This observational study was conducted retrospectively with a population and sample of all pelvic fracture patients in the emergency room at Dr. Kariadi Hospital Semarang for the period January 2021 to December 2023. The characteristics observed included gender, age, fracture classification, etiology, trauma score, fracture pattern, and management. and output. The data obtained is then presented descriptively. Results: A total of 34 patients with pelvic fractures were recorded in this study. There were 16 male patients and 18 female patients. A total of 3 patients were less than 17 years old, 19 patients were 17-34 years old, 7 patients were 35-52 years old and 3 patients were more than 52 years old. The most common cause of pelvic fractures was traffic accidents (KLL) with 28 patients, followed by work accidents (4 patients) and other trauma (2 patients). Based on the Young-Burgess classification, the most common pelvic fracture pattern was LC1 (11 patients), followed by APC1 (3 patients), APC2 (4 patients), APC3 (3 patients), LC2 (2 patients), LC3 (6 patients), VS (4 patients), and CM (1 patient). A total of 4 patients had an ISS score of 1-8, 8 patients had an ISS score of 9-15, 9 patients had an ISS score of 16-25, and 13 patients had an ISS score of more than 25. The most common accompanying injury was long bone fracture (15 patients), head injury in 10 patients, abdominal trauma in 9 patients, and thorax trauma in 4 patients. Operative treatment was carried out in 21 patients, while 13 other patients were treated non-operatively. Of the 34 patients, 8 patients died and 26 others were discharged in good condition. Conclusion: Most pelvic fractures occur at the age of 17-34 years and the most common cause is KLL. All pelvic fracture patients had concomitant injuries and the majority of patients had unstable fractures that required operative treatment. Mortality due to pelvic fracture and/or accompanying injuries is 23.5%.